2022
DOI: 10.1002/celc.202101654
|View full text |Cite
|
Sign up to set email alerts
|

The Cycle Stability and Rate Performance of LiNi0.8Mn0.1Co0.1O2 Enhanced by Mg Doping and LiFePO4 Coating

Abstract: Nickel‐rich layered oxide LiNi0.8Mn0.1Co0.1O2 became one of the preferred cathode materials for lithium‐ion batteries because of its advantages in capacity, cost and environmental protection. However, increased nickel content inevitably leads to more serious structural deterioration, such as irreversible phase transition, unexpected side effects as well as Li+/Ni2+ mixing, etc. This results in poor cycle stability and rate performance. Herein, we proposed a co‐modification strategy for Mg doping and LiFePO4 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…In their study, Zhang et al 130 . employed a dual approach involving magnesium ion doping and a coating of LiFePO 4 to enhance the cyclability and rate performance of nickel‐rich oxides (Figure 10A).…”
Section: Modification Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In their study, Zhang et al 130 . employed a dual approach involving magnesium ion doping and a coating of LiFePO 4 to enhance the cyclability and rate performance of nickel‐rich oxides (Figure 10A).…”
Section: Modification Methodsmentioning
confidence: 99%
“…Reproduced with permission. 130 Copyright 2022, John Wiley and Sons. (B) Charge and discharge curves of the original and modified samples at 0.2C.…”
Section: Dual Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…To solve this issue, researchers have introduced lithium-containing compounds with high Li + conductivity for surface modification. These compounds include LiCoO 2 [184], LiNi 0.333 Co 0.333 Mn 0.333 O 2 [185], Li 2 ZrO 3 [186][187][188], LiZr 2 (PO 4 ) 3 [189], LiAlO 2 [190], Li 2 SiO 3 [191], Li 2 MnO 3 [192], LiNbO 3 [193,194], LiFePO 4 [195,196], Li 3 PO 4 [197][198][199], LiH 2 PO 4 [200], LiBO [201,202], and LLAO [203]. Yang et al [188] utilized the Couette-Taylor reaction to deposit a surfacecoated Li 2 ZrO 3 layer onto LiNi 0.90 Co 0.04 Mn 0.03 Al 0.03 O 2 (NCMA), with a thickness of approximately 2.5 nm.…”
Section: Interfacial Modification By Surface Coatingmentioning
confidence: 99%
“…Experimental results also showed that coating modification effectively improved the cycling stability of NCM811, increasing the capacity retention rate from 19% to 70% after 500 cycles. Zhang et al [196] introduced a modification strategy of Mg doping and LiFePO 4 coating on NCM811. The modified cathode displayed lower charge transfer resistance than the original material.…”
Section: Interfacial Modification By Surface Coatingmentioning
confidence: 99%